Identification and Analysis of p53-Regulated Enhancers in Hepatic Carcinoma - Zhang, Yin; Qian, Mingming; Tang, Fei; Huang, Qingqing; Wang, Wenzhu; Li, Yanjing; Li, Zhixue; Li, Beiping; Qiu, Zhengliang; Yue, Junjie; Guo, Zhiyun (Frontiers in Bioengineering and Biotechnology, 2020)
Enhancers can act as cis-regulatory elements to control transcriptional regulation by recruiting transcription factors (TFs) in a distance and orientation-independent manner. However, it is still unclear how p53 participates in the enhancer network as TF in hepatic carcinoma under the condition of DNA damage. A total of 14,286 activate enhancers were identified through the integration of stable and unstable enhancer RNAs (eRNAs) captured by CAGE and GRO-seq, respectively. Furthermore, 218 p53-bound enhancers (Enhp53) were identified by analyzing p53 ChIP-seq in HepG2 cells after DNA damage. The results showed that the enhancer expression and histone markers of enhancers (H3K4me1, H3K4me2, H3K4me3, H3K9ac, and H3K27ac) revealed significantly higher level on Enhp53 than Enhno-p53 which suggested that p53 participated in regulating enhancer activity and chromatin structure. By analyzing 124 TFs ChIP-seq from ENCODE, 93 TFs were found significantly enriched on Enhp53 such as GATA4, YY1 and CTCF, indicating p53 may co-regulate enhancers with TFs participation. Moreover, significantly differentially expressed 438 miRNAs and 1,264 mRNAs were identified by analyzing small RNA-seq and RNA-seq, and 26 Enhp53-miRNAs and 145 Enhp53-mRNA interactions were identified by the integration of 3D genome data and genomic distance. The functional enrichment analysis showed that these miRNA targets and mRNAs were significantly involved in tumor biological processes and signaling pathways such as DNA replication, p53 signaling pathway, hepatitis B, focal adhesion, etc. The above results indicated that p53 participated in regulating enhancer network in hepatic carcinoma and Enhp53 exhibited significantly different signatures with Enhno-p53.